Explorando reações de funcionalização C(sp2)-H fotocatalisadas por porfirinas em condições de fluxo contínuo e o uso da eletrocatálise para promover acoplamentos C-S - Matos, Aline Aparecida Nunes Souza de (2021)
Photoarylation reactions (Chapter I) were studied in both batch and continuous flow conditions starting from arenodiazonium salts and activated olefins to yield α-aryl ketones/aldehyde derivatives. Such reactions were mediated by the use of porphyrin derivatives as photocatalysts via SET. Motivated by the fact that porphyrin derivatives are poorly explored molecules in SET photocatalysis, this research project was conceived with the aim of developing a new synthetic methodology. Photophysical and electrochemical studies of the porphyrin derivatives used in this study allowed us to understand their behavior in the photoredox cycle. Reactions in continuous flow conditions were applied in both methodological developments, scope and scale-up (30 mmol scale), which resulted in improvements to the process, efficiency, and safety. The photochemical reactors used in this study were designed and built for this project. In chapter II, we attempted to apply the methodology developed in the first phase of the study to the synthesis of two building blocks, which are API’s intermediates of Raloxifene and Elagolix. Different photoredox conditions were explored to favor the formation of the desired scaffolds, namely, the benzothiophene (Raloxifene) and an uracil derivative (Elagolix). However, it was not possible to obtain the desired compounds with success. In chapter III, electrochemical sulfenylation reactions were studied in galvanostatic conditions in both batch and continuous flow regimes, involving thiophenols/thiols and activated olefins to yield of α-arylthioketones. Studies with different electrolytes have shown that quaternary ammonium salts are the best mediators for this reaction. Notably, during the study of the reaction scope, a cysteine derivative proved to be extremely tolerant to our protocol. Unfortunately, due to a technical limitation of the electrochemical reactor (225µL, Syrris module), the continuous flow protocol was not effective, and the scope was explored only in batch.